67 A BLENDED MODEL OF CARE USED IN THE ROLLOUT OF AN EARLY SUPPORTED DISCHARGE FOR STROKE SERVICE DURING COVID-19. (18th November 2021) - Reilly, E; Jana, W; Dwyer, S; Donohoe, A; Crowley, A; Foley, S
Abstract: Background: The Health and Social Care Professionals budget was augmented to develop rehabilitation services that facilitated hospital discharges. Early Supported discharge (ESD) for stroke is a proven model of best care for stroke patients with mild to moderate disability (Langhorne et al., 2005). A pilot was implemented with the team consisting of an Occupational Therapist, Speech and Language Therapist, Physiotherapist and Medical Social Worker. Methods: The service facilitated an early discharge from the hospital with the delivery of specialist stroke rehabilitation in the home. Therapy is provided with the same intensity and expertise that would be received in hospital and is available for up to 8 weeks, it was provided using a blended model of domiciliary care and the introduction of telehealth in response to COVID 19. Data was recorded for 100 service users using an excel spreadsheet. Data was recorded to measure number of new referrals, length of stay, bed days released back into the hospital system, mode of service delivery and functional outcomes. A cost analysis was completed. Service user experience was captured using questionnaires. Results: From September 2020 to July 2021, 100 patients accessed ESD with a reduction of 7.2 days in hospital stay per patient. Improvements in pre- and post- rehabilitation scores on the FIM/FAM were evident. Very positive feedback regarding the rehabilitation experience was captured within the patient satisfaction questionnaire. Therapy delivery was 60% face to face, 37% via telehealth and 3% outpatient appointments. Telehealth received good compliance but with varying reports of experience in comparison to face to face. Conclusion: ESD provided in the home environment facilitated earlier discharge from hospital with positive outcomes for the hospital and service users. Telehealth ensured that rehabilitation was maintained throughout the pandemic. Telehealth increased access for patients residing outside of the catchment area. However service user preference remains face to face.